Perancangan Sport Center Dengan Pendekatan Desain Universal di Labuhanbatu Utara - Adinda Tara; Wahyuni Zahra (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
A sports center is a place that accommodates various types of sports activities that can increase a person's physical, mental and social potential in certain fields in a region. The aim of this research is to design a suitable sports center by creating a friendly and inclusive environment for all users and minimizing accessibility barriers. Designing a sports center can be a forum for all users by paying attention to several factors and supporting architectural elements by applying Universal Design principles. The research method used is a qualitative method through ideas by collecting data which includes literature studies and case studies of typologies or similar themes, then followed by analysis as a design guide. The results of the study of the application of the universal design concept to the design of sports centers by applying the principles of universal design, namely the existence of special paths for disabled users, ramps that will be used as a means of vertical connection between floors, providing accessible places for wheelchair users, making signs and clear information so that visitors can access it more easily, creating open circulation that is safe and comfortable for visitors.